ARE ALL THE PROLONGED DRUG FORMULATIONS OF NIFEDIPINE THE SAME? - V. G. Kukes; D. A. Sychev (Рациональная фармакотерапия в кардиологии, 2016)
Publication is devoted to the calcium antagonist nifedipine in drug formulations of the prolonged action. Comparison of technological peculiarities of these formulations is given, pharmacokinetic and pharmacodynamic effects are reviewed. Data about therapeutic effects of nifedipine in different forms of the prolonged action at arterial hypertension and stable angina are observed. Questions of treatment safety are discussed. Conclusion about advantages of nifedipine in the formulation of gastrointestinal therapeutic system (GITS) is made.